2013
DOI: 10.1371/journal.pone.0059281
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Pharmacological Characterization of Angiostatin Release and Generation by Human Platelets: Implications for Endothelial Cell Migration

Abstract: Platelets play an important role in thrombosis and in neo-vascularisation as they release and produce factors that both promote and suppress angiogenesis. Amongst these factors is the angiogenesis inhibitor angiostatin, which is released during thrombus formation. The impact of anti-thrombotic agents and the kinetics of platelet angiostatin release are unknown. Hence, our objectives were to characterize platelet angiostatin release temporally and pharmacologically and to determine how angiostatin release influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
(41 reference statements)
0
19
0
1
Order By: Relevance
“…One proposed mechanism by which it may promote angiogenesis is by the inhibition of angiostatin generation by platelets (38, 39). Angiostatin induces apoptosis in and inhibits migration of endothelial cells (39), and is formed by the auto-proteolysis of plasmin (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed mechanism by which it may promote angiogenesis is by the inhibition of angiostatin generation by platelets (38, 39). Angiostatin induces apoptosis in and inhibits migration of endothelial cells (39), and is formed by the auto-proteolysis of plasmin (38).…”
Section: Discussionmentioning
confidence: 99%
“…One proposed mechanism by which it may promote angiogenesis is by the inhibition of angiostatin generation by platelets (38, 39). Angiostatin induces apoptosis in and inhibits migration of endothelial cells (39), and is formed by the auto-proteolysis of plasmin (38). As an inhibitor of serine proteases (including plasmin), aprotinin has been shown to inhibit angiostatin generation by platelets and subsequently induce an increased angiogenic response (38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-documented that angiostatins induce anoikis and apoptosis and inhibit proliferation and migration of endotheliocytes, thus restrict vessel tube formation and neovascularization [6,7]. Currently, numerous reports indicate that various cell types are able to gene rate angiostatins in relatively high amounts [8,9]. In the previous papers, angiostatins are described as constantly formed by several types of retina-resident cells [10].…”
Section: The Purpose Of the Present Study Was To Examine The Plasminomentioning
confidence: 99%
“…Some authors have found that platelets constitutively generate angiostatins, internalize, store, and release them upon activation [24]. Plateletderived angiostatins are thought to counterbalance angiogene sis stimulatory effects, including VEGF signalling [25].…”
Section: Fragmentation Of Glu-plasminogen By the Whole Platelets (Amentioning
confidence: 99%